Neural Food Reward Processing in Successful and Unsuccessful Weight Maintenance. Issue 5 (23rd April 2018) - Simon, Joe J.; Becker, Alexandra; Sinno, Maria Hamze; Skunde, Mandy; Bendszus, Martin; Preissl, Hubert; Enck, Paul; Herzog, Wolfgang; Friederich, Hans‐Christoph
Abstract : Objective: Weight loss maintenance is one of the biggest challenges in behavioral weight loss programs. The present study aimed to examine metabolic influences on the mesolimbic reward system in people with successful and unsuccessful long‐term weight loss maintenance. Methods: Thirty‐three women with obesity at least 6 months after the completion of a diet were recruited: seventeen women were able to maintain their weight loss, whereas sixteen showed weight regain. Using functional magnetic resonance imaging in combination with the assessment of appetite‐regulating hormones, neural reward processing during hunger and satiety was investigated. An incentive delay task was employed to investigate the expectation and receipt of both food‐related and monetary reward. Results: Only participants with successful weight loss maintenance showed a satiety‐induced attenuation of brain activation during the receipt of a food‐related reward. Furthermore, in successful weight loss maintenance, the attenuation of active ghrelin levels was related to brain activation in response to food‐related reward anticipation during satiety. Conclusions: The findings suggest that an attenuated influence of satiety signaling on the neural processing of food‐related reward contributes to unsuccessful weight loss maintenance. Thus, intact satiety signaling to the mesolimbic reward system may serve as a promising target for tackling weight cycling.